Treatment for Schistosoma japonicum, reduction of intestinal parasite load, and cognitive test score improvements in school-aged children. - Amara E Ezeamama; Stephen T McGarvey; Joseph Hogan; Kate L Lapane; David C Bellinger; Luz P Acosta; Tjalling Leenstra; Remigio M Olveda; Jonathan D Kurtis; Jennifer F Friedman (Public Library of Science (PLoS), 2012)
To determine whether treatment of intestinal parasitic infections improves cognitive function in school-aged children, we examined changes in cognitive testscores over 18 months in relation to: (i) treatment-related Schistosoma japonicum intensity decline, (ii) spontaneous reduction of single soil-transmitted helminth (STH) species, and (iii) ≥2 STH infections among 253 S. japonicum-infected children.Helminth infections were assessed at baseline and quarterly by the Kato-Katz method. S. japonicum infection was treated at baseline using praziquantel. An intensity-based indicator of lower vs. no change/higher infection was defined separately for each helminth species and joint intensity declines of ≥2 STH species. In addition, S. japonicum infection-free duration was defined in four categories based on time of schistosome re-infection: >18 (i.e. cured), >12 to ≤18, 6 to ≤12 and ≤6 (persistently infected) months. There was no baseline treatment for STHs but their intensity varied possibly due to spontaneous infection clearance/acquisition. Four cognitive tests were administered at baseline, 6, 12, and 18 months following S. japonicum treatment: learning and memory domains of Wide Range Assessment of Memory and Learning (WRAML), verbal fluency (VF), and Philippine nonverbal intelligence test (PNIT). Linear regression models were used to relate changes in respective infections to test performance with adjustment for sociodemographic confounders and coincident helminth infections.Children cured (β = 5.8; P = 0.02) and those schistosome-free for >12 months (β = 1.5; P = 0.03) scored higher in WRAML memory and VF tests compared to persistently infected children independent of STH infections. A decline vs. no change/increase of any individual STH species (β:11.5-14.5; all P<0.01) and the joint decline of ≥2 STH (β = 13.1; P = 0.01) species were associated with higher scores in WRAML learning test independent of schistosome infection. Hookworm and Trichuris trichiura declines were independently associated with improvements in WRAML memory scores as was the joint decline in ≥2 STH species. Baseline coinfection by ≥2 STH species was associated with low PNIT scores (β = -1.9; P = 0.04).Children cured/S. japonicum-free for >12 months post-treatment and those who experienced declines of ≥2 STH species scored higher in three of four cognitive tests. Our result suggests that sustained deworming and simultaneous control for schistosome and STH infections could improve children's ability to take advantage of educational opportunities in helminth-endemic regions.